Synthesis and properties of long [n]cumulenes (n ≥ 5) - Januszewski, Johanna; Tykwinski, Rik (Chemical Society Reviews, 2014)
Molecules composed of a contiguous sequence of double bonds, the [n]cumulenes, share structural similarities to both of their conjugated relatives, the polyenes and polyynes. The synthesis and properties of [n]cumulenes are, however, quite different from those of either polyenes or polyynes. At an infinite length, [n]cumulenes would provide one structural form of the hypothetical sp-hybridized carbon allotrope carbyne, while shorter derivatives offer model compounds to help to predict the properties of carbyne. Finally, derivatization of the π-electron framework of [n]cumulenes provides a number of different synthetic transformations, with cycloaddition reactions being the most common. In this review, both historical and recent synthetic achievements toward long [n]cumulenes (n ≥ 5) are discussed. This is followed by a description of our current understanding of the physical and electronic structure of [n]cumulenes based on UV/vis spectroscopy and X-ray crystallography. Finally, the reactivity of long [n]cumulenes is described. This journal is © the Partner Organisations 2014.